1.Zapisz wyrażenie, nie używając nawiasów.Zredukuj wyrazy podobne.

d) -(3a+6)-4
e) -(2x-1)-(3x+1)
f) (4a-7b)-(2a+3b)
g) (2p-r)+(2r-p)
h) (x+y)+(x-z)+(z-y)

4.Zapisz w jak najprostszej postaci.
a) (x-2)-(2-x)
b) (a+b)+(2a-b)-(a-2b)
c) (3x-y+1)-(x+y)+(y-x)
d) -(2a²-3ab)-(2b-3a²)+(-ab-b)

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-15T21:30:25+01:00
1.
d) -(3a+6)-4 = -3a-6-4 = -3a-10
e) -(2x-1)-(3x+1) = -2x+1-3x-1 = -5x
f) (4a-7b)-(2a+3b) = 4a-7b-2a-3b = 2a-10b
g) (2p-r)+(2r-p) = 2p-r+2r-p = p+r
h) (x+y)+(x-z)+(z-y) = x+y+x+z+z-y= 2x+2z

4.
a) (x-2)-(2-x) = x-2-2+x = 2x-4
b) (a+b)+(2a-b)-(a-2b) = a+b+2a-b-a+2b = 2a+2b
c) (3x-y+1)-(x+y)+(y-x) = 3x-y+1-x-y+y-x = x-y+1
d) -(2a²-3ab)-(2b-3a²)+(-ab-b) = -2x²+3ab-2b-3a²-ab-b = -3a²-2x²+2ab-3b
2010-03-15T21:33:46+01:00
1 d -3a-6-4= -3a-10
e) -2x+1-3x-1= - 5x
f) 4a-7b - 2a -3b= 2a - 10b
g) 2p -r + 2r-p= p+r
h) x+y+x-z+z-y= 2x

2
a) x-2-2+x= 2x -4
b) a+b + 2a-b -a+2b= 2a+2b
c) 3x-y+1-x-y+y-x= x-y+1
d) -2a2-+ 3ab- ab+3a2- ab-b= a2+ab -b

2010-03-15T21:38:43+01:00
1. d) -3a-6-4=-3a-10
e)-2x+1-3x-1=-5x
f) 4a-7b-2a-3b= 2a-10b
g)2p-r+2r-p=p+r
h)x+y+x-z+z-y=2x

4.a) x-2-2+x=-4
b)a+b+2a-b-a+2b=2a+2b
c)3x-y+1-x-y+y-x= x-y+1
d)2a²+2ab-3b